Phytochemical studies on stemona plants: Isolation of new tuberostemonine and stemofoline alkaloids - Thanapat Sastraruji (2018)
Two new tuberostemonine alkaloids, tuberostemonine L (3) and tuberostemonine M (4) and a new stemofoline alkaloid, (3'S)-hydroxystemofoline (5), along with two known alkaloids, (2'S)-hydroxystemofoline (1) and neotuberostemonine (2) have been isolated from a root extract of an unidentified Stemona species (Stemona sp.). The structure and relative configuration of these new alkaloids has been determined by spectral data interpretation, while the 3'S configuration of 5 was determined from NMR analysis of its (R)- and (S)-Mosher esters.